Measurement of the impact of music festivals on destination image: the case of a womad festival - Duarte, Paulo (2018)
This study sought to evaluate, in the context of the commercialization strategies of tourism destinations, if investment in cultural activities such as the organization of a well-known music festival can promote the creation and development of the host destination's image. After a review of the relevant literature, an analysis was done of the responses of tourists who attended the 2013 World of Music, Arts, and Dance Festival in Cáceres, Spain. The fieldwork involved a personal interview survey carried out during the event, whereby 301 valid questionnaires were obtained, which were processed using a structural equations model and the partial least squares method. The results show how the brand positioning of a music festival can contribute to creating a positive destination image for participating tourists. The findings have significant implications for managers in terms of music festival tourism, such as the need to emphasize the destination as a unique event setting.